A Systematic Review of Islamic Terrorist Webpages and Keywords - Al-Sukhni, H.A.H.; Ahmad, A.; Madihah Mohd Saudi (Universiti Sains Islam Malaysia, 2024)
As the internet is considerably expanding and on-line information is increasing, the identification and detection of the large amounts of different web information become vitally important, particularly those of dark web or Islamic extremists. Webpages with extremist and terrorist content are believed to be the main factors in the radicalisation and recruitment of disaffected individuals who might be involved in terrorist activities at home or those who fight alongside terrorist groups abroad. In fact, the sheer volume of online data makes it practically impossible for authorities to carry out the individual examination for every webpage, post or conversational thread that might or might not be relevant to terrorism or contain terrorist sympathies. As terrorists exist within every nation and every religion, hence this paper presents a review and systematic analysis of existing webpages on Islamic terrorists. This include existing database of Islamic extremist words and existing techniques of web classifier for keywords. Based on this systematic review analysis, it will be the input to the formation of a new Islamic extremists WorldNet.